Exercise as therapy for neurodevelopmental and cognitive dysfunction in people with a Fontan circulation: A narrative review - Verrall, Charlotte Elizabeth; Tran, Derek Lee; Yang, Joseph Yuan-Mou; Lubans, David Revalds; Winlaw, David Scott; Ayer, Julian; Celermajer, David; Cordina, Rachael (Frontiers in Pediatrics, 2023)
People with a Fontan circulation are at risk of neurodevelopmental disability and cognitive dysfunction that has significant implications for academic and occupational attainment, psychosocial functioning, and overall quality of life. Interventions for improving these outcomes are lacking. This review article discusses current intervention practices and explores the evidence supporting exercise as a potential intervention for improving cognitive functioning in people living with a Fontan circulation. Proposed pathophysiological mechanisms underpinning these associations are discussed in the context of Fontan physiology and avenues for future research are recommended.